Kuat Tekan Mortar OPC Dan Kerang Lokan Di Lingkungan Air Laut (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The compressive strength of concrete is defined as the ability of concrete to accept compressive force per unit area. The compressive strength is very important to study because it governs the suitable material composition needed for concrete mix. Damage that occurs  in concrete placed on corrosive environmet sea water, was trigged by salt that diffuse the concrete’s pore. After that, corrosion will occur cause weathering of the concrete reinforcement and the release of the material. The content of CaO in the lokan shells makes the shells have calcium binding on concrete or mortar mixture. This study aims to examine the compressive strength of Ordinary Portland Cement (OPC) mortar and  mortar with lokan seashells immersed in seawater environments. Powder from lokan sea shells was extracted  that was burned at high temperatured and filtered using sieve no 200.  The composition of powder content of lokan sea shell was 0 %, 2.5%, 5%, 7,5% and  10% of the weight of cement.   The specimen was in 5 x 5 x 5 cm cubes and cured on fresh water for 28 days. Later, these specimen were immersed in sea water environment for 3, 7 and 28 days. The results showed that the compressive strength of OPC mortar with lokan sea shells was higher than the compressive strength of OPC mortar. For the case of OPC mortar containing 10% of lokan sea shells, the addition of lokan sea shells powder casted increase compressive strength up to 6.5%   Keywords: Lokan seashell powder, compressive strength, OPC